2009
DOI: 10.1111/j.1600-0838.2009.00911.x
|View full text |Cite
|
Sign up to set email alerts
|

Potent inhibition of cartilage biosynthesis by coincubation with joint capsule through an IL‐1‐independent pathway

Abstract: The reason for the increased risk for development of osteoarthritis (OA) after acute joint trauma is not well understood, but the mechanically injured cartilage may be more susceptible to degradative mediators secreted by other tissues in the joint. To establish a model for such interactions, we coincubated bovine cartilage tissue explants together with normal joint capsule and found a profound (~70%) reduction in cartilage proteoglycan biosynthesis. This reduction is due to release by the joint capsule of a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 31 publications
3
21
0
Order By: Relevance
“…Etanercept (a TNF-α soluble receptor, CPGJ-pharm, China, 25 μg/ml), DB-1 (a mouse anti-rat IFN-γ monoclonal antibody, IgG1, 20 μg/ml) and α-IL-17 antibody (a rabbit anti-rat IL-17 antibody, IgG, Santa Cruz, 20 μg/ml) were administrated to T cell conditioned medium accordingly [25][26][27]. FLS were seeded in 6-well plates at a density of 10 5 /well and incubated with PPT medium or control medium for 24 h with or without the above blocker accordingly, and the isotype-matched IgG control were used as controls.…”
Section: Cytokine Blocker Treatmentmentioning
confidence: 99%
“…Etanercept (a TNF-α soluble receptor, CPGJ-pharm, China, 25 μg/ml), DB-1 (a mouse anti-rat IFN-γ monoclonal antibody, IgG1, 20 μg/ml) and α-IL-17 antibody (a rabbit anti-rat IL-17 antibody, IgG, Santa Cruz, 20 μg/ml) were administrated to T cell conditioned medium accordingly [25][26][27]. FLS were seeded in 6-well plates at a density of 10 5 /well and incubated with PPT medium or control medium for 24 h with or without the above blocker accordingly, and the isotype-matched IgG control were used as controls.…”
Section: Cytokine Blocker Treatmentmentioning
confidence: 99%
“…These cytokines are known to upregulate chondrocyte gene expression of various aggrecanases, collagenases and other MMPs, which are hypothesized to contribute to the degradation of cartilage matrix. In complementary in vitro models of acute joint injury [911], injurious mechanical compression has been shown to cause chondrocyte apoptosis and necrosis, and to potentiate the effects of cytokine treatment on cartilage matrix degradation.…”
Section: Introductionmentioning
confidence: 99%
“…To explain the degradative activities of synovium on cartilage it was proposed that tissuebound IL-1 increased the basal proteoglycans degradation on human OA cartilage during co-culture with synovial membrane 53 . Patwari et al 34 suggest that the catabolic pathways in chondrocytes induced during co-culture with cut synovium may be independent of the pro-inflammatory cytokines (IL-I and TNF-a), the inflammatory mediators secreted by synovium probably correspond to heat labile factors with a molecular weight of $20 kDa. In our study, we observed in the sheep model that without LPS, synovial explants added to cartilage explants increased basal expression of PGE 2 and cartilage GAG loss, in agreement with observations made by others using explants isolated from bovine 33 or human 53 joints.…”
Section: Discussionmentioning
confidence: 98%
“…Few efficacy studies of chondroprotective drugs used co-culture model of cartilage and synovial tissue 51,52 although it is well established that during in vitro culture, co-incubation of synovial membrane with cartilage generates soluble factors which accelerate matrix degradation [32][33][34] . To explain the degradative activities of synovium on cartilage it was proposed that tissuebound IL-1 increased the basal proteoglycans degradation on human OA cartilage during co-culture with synovial membrane 53 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation